Estrategias de fidelización del comercial jehová es mi pastor de la Parroquia Febres Cordero recinto La Teresa del cantón Babahoyo periodo 2023. - Ruiz García, Laura Yadira (2024)
In this case study was conducted to the Comercial Jehová is miy Pastor in the city of Babahoyo in the Recto. La Teresa, whose main objective is to develop loyalty strategies to increase sales, this study aims to keep existing customers satisfied and loyal, reducing the need to invest large sums of money in the acquisition of new customers, leading to greater profitability in the long term, the conduct of this research is to encourage the owner to establish loyalty strategies to achieve customer retention and have direct connection, applying all the recommendations already acquired and provide timely solution to the problem of this study, also a survey of frequent customers was conducted and the results were obtained as suggestions to generate loyalty with the business, concluding that by putting in first place the loyalty of customers to the business, will help the commercial Jehovah is my pastor in the first instance to improve the reputation, creating a personalized and continuous communication with future consumers, generating references and recommendations from them and thus optimize financial resources, and free from spending money on advertising campaigns to its target audience and in turn thanks to the loyalty strategies will increase their profits because they will have solid and loyal customers.